Biological agents for endoprosthetic joint replacement in patients with rheumatoid arthritis - Viktoria Nikolaevna Khlaboshina; V. N. Amirdzhanova (Современная ревматология)
Endoprosthetic replacement is a widely used treatment for joint disease worldwide. In the past few decades, the rate of endoprosthetic replacement of different joints has substantially increased – about 1.5 million operations yearly. The paper considers the problems of endoprosthetic joint replacement in patients with rheumatoid arthritis (RA) receiving biological agents (BAs). The latter are extensively used to treat not only the early, but also late stages of the disease when there are already indications for endoprosthetic joint replacement, but the activity of the disease cannot be diminished by standard therapy with disease-modifying antirheumatic drugs. BA therapy can enhance the efficiency of monitoring the activity of RA in its different stages and improve functional parameters. There is an increase in the number of patients requiring endoprosthetic joint replacement and receiving BAs. Data on the safety of BAs used in the perioperative period are given. Endoprosthestic joint replacement during this therapy makes it possible to decrease the degree of pain syndrome, to improve the function of an operated joint and the quality of life in patients, to affect the course of RA, to lower disease activity, and to improve their monitoring.